2014
DOI: 10.1080/14783363.2014.972626
|View full text |Cite
|
Sign up to set email alerts
|

Quality management in heavy duty manufacturing industry: TQM vs. Six Sigma

Abstract: Abstract'Is TQM a management fad?' This question has been extensively documented in the quality management literature; and will be tackled in this research though a critical literature review on the area. 'TQM versus Six-Sigma' debate, which has also been a fundamental challenge in this research filed, is addressed by a thematic and chronological review on the peer papers.To evaluate this challenge in practice, a primary research in heavy duty machinery production industry have been conducted using a case-stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Similarly, Nugroho & Nurcahyo (2018) also did a research in SME in Indonesia where they concluded that TQM implementation can improve the financial performance of SME. Sabet et al, (2014) did a study in UK manufacture company an they concluded that TQM is successfully improve the overall performance and it can be combined with Six Sigma to improve product quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Nugroho & Nurcahyo (2018) also did a research in SME in Indonesia where they concluded that TQM implementation can improve the financial performance of SME. Sabet et al, (2014) did a study in UK manufacture company an they concluded that TQM is successfully improve the overall performance and it can be combined with Six Sigma to improve product quality.…”
Section: Resultsmentioning
confidence: 99%
“…The average values have shown that, in practice, the best results in the eight TQM success factors are valid in the organizations of the private health sector that have implemented a QMS 49 Mensah et al, 2012 Business sector The study concluded that 3 factors that critical in implementing TPM successfully are: (1) top management commitment, (2) empowerment and involvement of employees, resource availability, (3) competition and increased customer awareness, and a well-functioning quality network 50 Sabet et al, 2014 Manufacturing sector…”
Section: Manufacturing Sectormentioning
confidence: 98%
“…Moreover, during this time, several competing and to some extent, related and complementary concepts were introduced and popularized in the management knowledge market. For example, Six Sigma is an example of a related concept (Goeke and Offodile 2005;Sabet et al 2016), which Green (2006) argues breathed new life into TQM and contributed to a revival of TQM through the use of "fresh" and non-contaminated labels (cf. Benders and Van Veen 2001).…”
Section: Current Statusmentioning
confidence: 99%
“…based on TQM and performance measurement principles' use the term 'continuous quality improvement' in reference to Deming's philosophy of 'a continual drive toward process improvement, specifically focused on targeting the mean and reducing the variation of the distribution of process output' (p. 113). Sabet, Adams, and Yazdani (2014) presented that TQM could enable 'systematic and continuous quality improvement' (p. 9), but requiring the integration of Six Sigma in order to focus and sustain improvements. Sousa and Aspinwall (2010) provide a complementary perspective, highlighting the role of performance measurement, in promoting, sustaining and demonstrating QI activities.…”
Section: Continuous and Quality Improvementmentioning
confidence: 98%